Respiratory Trajectories in Type 2 and 3 Spinal Muscular Atrophy in the iSMAC Cohort Study. (26th January 2021) - Trucco, Federica; Ridout, Deborah; Scoto, Mariacristina; Coratti, Giorgia; Main, Marion L.; Muni Lofra, Robert; Mayhew, Anna G.; Montes, Jacqueline; Pane, Marika; Sansone, Valeria; Albamonte, Emilio; D'Amico, Adele; et al.
Abstract : Objective: To describe the respiratory trajectories and their correlation with motor function in an international pediatric cohort of patients with type 2 and nonambulant type 3 spinal muscular atrophy (SMA). Methods: This was an 8-year retrospective observational study of patients in the International SMA Consortium (iSMAc) natural history study. We retrieved anthropometrics, forced vital capacity (FVC) absolute, FVC percent predicted (FVC%P), and noninvasive ventilation (NIV) requirement. Hammersmith Functional Motor Scale (HFMS) and revised Performance of Upper Limb (RULM) scores were correlated with respiratory function. We excluded patients in interventional clinical trials and on nusinersen commercial therapy. Results: There were 437 patients with SMA: 348 with type 2 and 89 with nonambulant type 3. Mean age at first visit was 6.9 (±4.4) and 11.1 (±4) years. In SMA type 2, FVC%P declined by 4.2%/y from 5 to 13 years, followed by a slower decline (1.0%/y). In type 3, FVC%P declined by 6.3%/y between 8 and 13 years, followed by a slower decline (0.9%/y). Thirty-nine percent with SMA type 2% and 9% with type 3 required NIV at a median age 5.0 (1.8–16.6) and 15.1 (13.8–16.3) years. Eighty-four percent with SMA type 2% and 80% with type 3 had scoliosis; 54% and 46% required surgery, which did not significantly affect respiratory decline. FVC%P positively correlated with HFMS and RULM scores in both subtypes. Conclusions: In SMA type 2 and nonambulant type 3, lung function declines differently, with a common leveling after age 13 years. Lung and motor function correlated in both subtypes. Our data further define the milder SMA phenotypes and provide information to benchmark the long-term efficacy of new treatments for SMA.